Equity research: Skechers U.S.A., Inc. - "facing future with comfort" - Paris, Pedro Maria (2022)
This Work Project analyses Skechers business and performance inside the Footwear industry and forecasts the results for the following periods given the current context ,risks, trends, and expectations. This work project concludes with a BUY recommendation on SKX stock with a target price for FY22 of $58.83, representing a 36.5% return for an investor holding the stock for a 12-month period.